PENGARUH PERBEDAAN JENIS KELAMIN TERHADAP FREKUENSI NAFAS, DENYUT JANTUNG, SUHU SHANK, DAN SUHU REKTAL AYAM KUB - Lukman Hakim; Khaira Nova; Purnama Edy Santosa; RR Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of sex differences on the physiology of chickens including respiratory frequency, heart rate, shank temperature, and rectal temperature of KUB chickens. The research was conducted on 10--16 August 2017 at Cage Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. This study used 50 chickens (25 males and 25 females) aged 13 weeks with an average weight of 850 g. Data were collected after measuring the temperature and humidity at 08.00-17.00 for 3 consecutive days to determine the extreme temperature of the environment. The variables in this study were respiratory rate, heart rate, shank temperature, and rectal temperature of KUB chickens at extreme temperatures. The results were analyzed using the t-test at the 5% significance level. The t-test results showed that the sex of KUB chickens had no significant effect on respiratory frequency, heart rate, shank temperature, and rectal temperature. Key words : Chicken physiological, KUB chicken, Sex type